Alcohol and illicit drug use in people with diabetes. Issue 3 (March 2020) - Pastor, Adam; Conn, Jennifer; MacIsaac, Richard J; Bonomo, Yvonne
Summary: As the prevalence of type 1 and type 2 diabetes increases and population-level patterns of alcohol and illicit drug use evolve, clinicians will continue to encounter people with diabetes whose substance use is affecting health outcomes. Substance use contributes substantially to the population-level prevalence of cardiovascular events, cerebrovascular events, cancers, mental health conditions, road trauma, and domestic violence. Alcohol and drug use also have a measurable effect on diabetes incidence and the development of both acute and chronic diabetes-related complications. In this Review, we examine the effect of alcohol and illicit drug use on people with type 1 or type 2 diabetes. We describe evidence for substance use as a risk factor for new-onset diabetes, prevalence of use in people with diabetes, evidence linking substance use with diabetes-related health outcomes, and evidence on the management of these co-occurring conditions.